Insects and Other Arthropods of Tropical America - Hanson, Paul E.; Hanson, Paul E.; Nishida, Kenji 1972- (Book collections on Project MUSE., 2016)
"Describes the principal insect groups and other arthropods encountered in a tropical forest in the Americas, and is an introduction to the natural history of insects and other arthropods" ...